ACUTE POLYUMERIA SYNDROME INDUCED BY DEXMEDETOMIDINE DURING SPINAL NEUROSURGERY (clinical observation) - A. V. Solenkova; O. N. Ivanova; A. M. Аrefiev; A. Yu. Lubnin; N. A. Konovalov; V. A. Korolishin; S. Yu. Timonin (Вестник анестезиологии и реаниматологии)
Dexmedetomidine is a high-selective α2-agonist, which is used as an anesthetic component, and it is expected to induce polyuria. Initially, it was mainly used for sedation in emergency wards, and further this medicine got widespread use in anesthesiology. The major positive effect of dexmedetomidine is related to its central sympatholytic action and suppression of the activity of sympathetic nervous system. This medicine also provides a favorable hemodynamic profile. However, it has a number of certain disadvantages. The present clinical study reports development of acute polyuria syndrome due to the administration of dexmedetomidine during spinal neurosurgery.